Financial Repression, Liberalization, Crisis and Restructuring: Lessons of Korea's Financial Sector Policies - Yoon Je Cho (Asian Development Bank Institute (ADBI), 2002)
Koreas financial sector has gone through heavy repression, rapid liberalization, deep crises, and massive restructuring during the last half century. This paper discusses Koreas financial sector policies in relation to its real sector development, and attempts to draw some lessons from this dynamic experience. The main lessons may be summarized as follows. There is no best financial sector policy and practice that can be applied at all times. Financial sector policy is one of the most important policy measures that a state can employ for the goal of economic development. This policy may evolve gradually in accordance with the development of economic circumstances with ultimate evolution to a fully market-oriented policy. However, the recent global economic environment suggests that interventionist policies should be short-lived. As the domestic economy becomes more sophisticated and more integrated into the global economy, the negative impacts of such policies become more profound. However, system inertia often prevents timely adjustment of policy to one more suited to a changed environment. The outcomes in the real sector of a controlled financial sector, such as high corporate leverage ratios, also prevent the rapid liberalization of financial sector policies. While leaving the distorted incentive structure in the real sector intact, financial liberalization can even intensify the distorting effects of real sector problems. Thus, the sequencing and speed of financial reforms (and more broadly economic transition) becomes a key issue. Financial sector reform should be tuned to the progress of real sector reforms and the development of the financial market infrastructure and regulatory capacities. This sequencing and policy coordination issue is important not only in the process of financial liberalization, but also in the process of financial restructuring. The countries of East Asia, particularly Korea and the PRC, are facing the challenge of how to implement condensed liberalization and successful economic transition after having achieved condensed economic growth, in this rapidly integrating global economy. No international best practice has yet been established to guide successful and rapid economic transition.
hdl:11540/4152
Keywords: 330